Occurrence of sulfated fucose branches in fucosylated chondroitin sulfate are essential for the polysaccharide effect preventing muscle damage induced by toxins and crude venom from Bothrops jararacussu snake. (May 2015) - Monteiro-Machado, Marcos; Tomaz, Marcelo A.; Fonseca, Roberto J.C.; Strauch, Marcelo A.; Cons, Bruno L.; Borges, Paula A.; Patrão-Neto, Fernando C.; Tavares-Henriques, Matheus S.; Teixeira-Cruz, Jhonatha M.; Calil-Elias, Sabrina; Cintra, Adélia C.O.; Martinez, Ana Maria B.; et al.
Abstract: Snake envenoming is an important public health problem around the world, particularly in tropics. Beyond deaths, morbidity induced by snake venoms, such as myotoxicity, is of pivotal consequence to population. Bothrops jararacussu is the main venomous snake in southeast region of Brazil, and particularly presents strong myotoxic effect. The only available therapy, antibothropic antivenom, poorly affects venom-induced myotoxicity. The aim of this study is to assess the ability of fucosylated chondroitin sulfate (fucCS), a glycosaminoglycan with anticoagulant and antithrombotic properties, and its derivatives to inhibit toxic activities of B. jararacussu crude venom and its isolated toxins, named bothropstoxins (BthTX-I and BthTX-II). The in vitro myotoxic activities induced by crude venom, by BthTX-I alone and by toxins together were abolished by fucCS. Carboxyl reduction (fucCS-CR) kept this ability whereas defucosilation (defucCS) abrogates myoprotection. We observed the same pattern in the response of these polysaccharides in antagonizing the increase in plasma creatine kinase (CK) levels, the reduction of skeletal muscle CK content and the rise of myeloperoxidase (MPO) activity induced by crude venom and isolated toxins. FucCS inhibited edematogenic activity and partially prevented the reduction of total leukocytes in blood when pre-incubated with crude venom. Furthermore, the venom procoagulant effect was completely antagonized by increasing concentrations of fucCS, although this polyanion could stop neither the tail bleeding nor the skin hemorrhage induced by Bothrops jararaca venom. The B. jararacussu phospholipase, hyaluronidase, proteolytic and collagenase activities were inhibited in vitro . The results suggest that fucCS could be able to interact with both toxins, and it is able to inhibit BthTX-II phospholipase activity. Light microscopy of extensor digitorum longus muscle (EDL) muscle showed myoprotection by fucCS, once necrotic areas, edema and inflammatory cells were all decreased as compared to venom injection alone. Altogether, data show that fucCS was able to inhibit myotoxicity and inflammation induced by B. jararacussu venom and its phospholipase toxins, BthTX-I and BthTX-II. Thus, fucosylated chondroitin sulfate is a new polyanion with potential to be used as an adjuvant in the treatment of snakebites in the future. Highlights: FucCS antagonized different in vitro and in vivo actions of Bothrops jararacussu venom. FucCS antagonized bothropstoxins phopholipase and myotoxic. Sulfated fucose branches of fucCS are essential for the prevention of muscle damage by B. jararacussu venom and toxins.